Tingkat Pengetahuan Anggota UKM Karate Unesa Terhadap Faktor Cedera, Pencegahan Dan Penanganan Cedera - Atmaja, Aditya Nindya; Yuliastrid, Dita; Susanto, Indra Himawan; Bakti, Ananda Perwira (Jurnal Porkes, 2024)
The purpose of this study was to assess the level of knowledge of Karate UKM members on injuries, injury prevention and injury management. This research method is descriptive quantitative with a sample of 30 people consisting of 20 men and 10 women using the whole sample. The data collection technique uses a questionnaire method with a Likert scale consisting of 40 questions. The results showed the level of knowledge of Karate UKM members on sports injury factors, sports prevention showed in the "medium" category. While the level of knowledge of UKM Karate members shows the "low" category. These results indicate that the level of knowledge of members is influenced by the level of concentration and interest when providing material related to injury and the difference in material between UKM, training ground and lectures. The conclusion of this study is that the level of knowledge of UKM Karate members on injury factors is in the medium category 53%. The level of knowledge of UKM Karate members on injury prevention is in the low category 37%. the level of knowledge of UKM Karate members on injury handling is in the moderate category 57%.